Correspondence regarding a 1916-22 Memorial to be erected in Cork under the terms of the J. J. Walsh bequest - O'Donoghue, Florence, 1895-1967; Twomey, Moss, 1896-1978; Lynch, Diarmuid, 1878-1950; Wrenne, Joseph F. 1889- (1950)
Includes a copy of J.J. Walsh's will. Correspondents include Moss Twomey, Diarmuid Lynch, J.F. Wrenne and others.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Walsh, J. J., -- 1880-1948; Ireland -- History -- 1922-